UBAIDULLAKHAN IS A TALENTED ARMY LEADER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This scientific article describes the unique, multifaceted talent of Shaybanizoda Ubaidullah Khan, his struggle against the Iranian Safavids, the battles of Kuli Malik and Gijduvan, the victory achieved, and its significance using sources. The place of Ubaidullah Khan in the history of Uzbek statehood is shown.